Charging and characterization of non-patterned organic micro electret arrays - Liu, Shuwei (2014)
This paper presents the charging and characterization of organic micro electret array for vibration energy harvesting. Micro sized electrets with stable and high surface potential are essential for long-term effectiveness of micro electrostatic power generators which harvest low-level vibration energy. In this study, a localized corona charging method to obtain micro sized electret areas on non-patterned macro sized dielectric thin film has been proposed to solve the problem of low charging efficiency and fast charge decay of micro sized electrets. This method involves using a shadow mask to transfer charge patterns and a triode corona charging configuration to facilitate charge penetration. Charging efficiency of 93.6% is achieved on an electret area of 100µm × 100µm, and 87% of its initial surface potential remains on the shrunken area of 50µm × 50µm after 240 days of storage. A technique combining SEM surface topography and non-contact measurement of the average surface potential has been developed to map the charge distribution on locally charged dielectric thin film and measure the surface potential on the micro sized charged area by incorporating the layout characteristic of an micro electret array.